2016
DOI: 10.1080/15548627.2016.1179405
|View full text |Cite
|
Sign up to set email alerts
|

TFEB and TFE3 cooperate in the regulation of the innate immune response in activated macrophages

Abstract: The activation of transcription factors is critical to ensure an effective defense against pathogens. In this study we identify a critical and complementary role of the transcription factors TFEB and TFE3 in innate immune response. By using a combination of chromatin immunoprecipitation, CRISPR-Cas9-mediated genome-editing technology, and in vivo models, we determined that TFEB and TFE3 collaborate with each other in activated macrophages and microglia to promote efficient autophagy induction, increased lysoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
327
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 261 publications
(356 citation statements)
references
References 49 publications
27
327
2
Order By: Relevance
“…4a, b). These results are consistent with observations by Pastore et al, who also observed delayed nuclear entry of these proteins in response to LPS-induced macrophage activation (Pastore et al, 2016). Strikingly, mRNA levels of TFEB and TFE3 target genes (i.e.…”
Section: Rapid Lysosome Expansion Is Not Dependent On Tfeb and Tfe3supporting
confidence: 82%
See 2 more Smart Citations
“…4a, b). These results are consistent with observations by Pastore et al, who also observed delayed nuclear entry of these proteins in response to LPS-induced macrophage activation (Pastore et al, 2016). Strikingly, mRNA levels of TFEB and TFE3 target genes (i.e.…”
Section: Rapid Lysosome Expansion Is Not Dependent On Tfeb and Tfe3supporting
confidence: 82%
“…5, 2018; Our results suggest that biosynthesis plays a major role in LPS-induced lysosome expansion in macrophages. Activation of TFEB and TFE3 transcription factors drives expression of lysosomal genes thereby stimulating lysosome function under various stresses including starvation, phagocytosis, protein aggregation and macrophage activation (Gray et al, 2016;Liu et al, 2017;Martina et al, 2014;Pastore et al, 2016;Polito et al, 2014;Raben and Puertollano, 2016;Sardiello et al, 2009;Settembre et al, 2012Settembre et al, , 2013. Thus, we next investigated whether the observed rapid lysosome expansion was driven by TFEB-and TFE3-mediated transcriptional upregulation of lysosome genes.…”
Section: Rapid Lysosome Expansion Is Not Dependent On Tfeb and Tfe3mentioning
confidence: 99%
See 1 more Smart Citation
“…To do this, RAW macrophages deleted for TFEB, TFE3 or both (Pastore et al, 2016) were treated with vehicle or apilimod for 1 h and manually assessed for the average diameter and number of swollen vacuoles using differential interference contrast (DIC) optics. As suspected, RAW cells carrying deletions for TFEB and/or TFE3 were not impaired in apilimod-induced vacuolation, with vacuole number and size comparable to wild-type RAW cells (Supplemental Fig.…”
Section: Pikfyve-inhibition Induces Lysosome Swelling Cells Deleted Fmentioning
confidence: 99%
“…For example, in macrophages and dendritic cells, lysosomes are transformed from individual puncta into a highly tubular network (Saric et al, 2016;Vyas et al, 2007;Swanson et al, 1987). In addition, nutrient depletion, protein aggregation, and phagocytosis activate a family of transcription factors that can enhance expression of lysosome genes and adjust lysosome activity (Gray et al, 2016;Pastore et al, 2016;Sardiello et al, 2009;Tsunemi et al, 2012;Medina et al, 2011;Settembre et al, 2012;Roczniak-Ferguson et al, 2012). This is best understood for the related transcription factors, TFEB and TFE3, which are recruited to the surface of lysosomes and subject to phosphorylation by various kinases including mTORC1 to modulate their nucleo-cytoplasmic transport (Li et al, 2016b;Martina et al, 2012;Peña-Llopis et al, 2011;Martina et al, 2014Martina et al, , 2016Roczniak-Ferguson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%